Hands-On Artificial Intelligence for Search Building Intelligent Applications and Perform Enterprise Searches - Patel, Devangini (Packt Publishing Ltd, 2018)
In this book, you will understand what artificial intelligence is. It explains in detail basic search methods: Depth-First Search (DFS), Breadth-First Search (BFS), and A* Search, which can be used to make intelligent decisions when the initial state, end state, and possible actions are known. Random solutions or greedy solutions can be found ...